The Second Split in Economic Science (About 2018 Nobel Memorial Prize in Economic Sciences) - Y. P. Voronov (Мир новой экономики, 2019)
In this article, I described the results of investigations achieved by two American economists William Nordhaus and Paul Romer. They have been awarded the 2018 Nobel Memorial Prize in Economic Sciences mainly for the introduction of feedbacks in economic and mathematical modelling. Nordhaus “for integrating climate change into long-run macroeconomic analysis” where quantitative model describes the global interplay between the economy and the climate and integrates theories and empirical results from physics, chemistry and economics. Romer “for integrating technological innovations into the long-run macroeconomic analysis” where he shows how knowledge can function as a driver of long-term economic growth.  I considered three blocks in the models of W. Nordhaus and P. Romer and the functions of each of them. Also, I discussed the assumptions that underlie their models. The author notes that climate change models are also being built in Russia, but there are no economic blocks in them, models of long-term economic growth with endogenous scientific and technological progress are formed in Russia also, but representatives of natural Sciences do not participate in them. Experience of the laureates shows that providing models of long-run economic development of the country and the world are necessary. The article also highlights P. Romer work on international Charter cities, the sources of world scientific and technological progress.